2021
DOI: 10.21203/rs.3.rs-999957/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metaproteomic Comparison of Cryoconite Communities from Caucasian and Novaya Zemlya Glaciers

Abstract: Anthropogenic pollution strongly affects glacial microbiological communities and promotes glacial melting. In the early stages of glacial melting formation of small cylindrical holes (cryoconite) occurs. While the microbiome of cryoconite is well described, the effect of anthropogenic pollution on cryoconite microbiological communities still has not been fully understood. Thus, we performed an unbiased functional comparison of the cryoconite communities from the highly polluted Caucasian glaciers and from less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It was also shown that microniсhes play an important role in the formation of the biodiversity of cryoconites [8]. Recently, the metaproteomic characterization of cryoconites has been provided for the rst time [9]. One of the important properties of cryoconites is polydispersity -they contain mineral and organic particles of various sizes, i.e., ecological microniches [10].…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that microniсhes play an important role in the formation of the biodiversity of cryoconites [8]. Recently, the metaproteomic characterization of cryoconites has been provided for the rst time [9]. One of the important properties of cryoconites is polydispersity -they contain mineral and organic particles of various sizes, i.e., ecological microniches [10].…”
Section: Introductionmentioning
confidence: 99%